AMARANTHUS (Amaranthus hybridus L.) RESPONSE TO COCOA POD HUSK POWDER AND NITROGEN FERTILISER APPLICATIONS - Akinrinola, Tajudeen B.; Salami, Adedayo O.; Adegoke, Samuel A. (Chilean Journal of Agricultural & Animal Sciences, 2025)
Amaranthus is a fast-growing vegetable affected by inadequate soil nutrient supply due to intensive cultivation. Inorganic fertiliser application reduces vegetable quality, thus, farm waste such as Cocoa pod husk (CPH) was encouraged as organic fertiliser. However, limited information is available on CPH powder or its combination with urea on amaranthus performance. Therefore, the response of amaranthus to CPH and urea fertiliser was investigated. In a replicated 3 × 3 factorial experiment, CPH powder at 0, 30, and 60 kg N ha-1 and urea fertiliser at 0, 30, and 60 kg N ha-1 were evaluated in a randomised complete block design with five replicates using 4 kg soil. Data collected were subjected to ANOVA and significantly different means were separated at p<0.05. The results indicated that the control (0 kg CPH) had better growth than the CPH-treated plants at both plantings. Applying 60 kg N ha-1 urea significantly increased the number of leaves and shoot biomass compared to the other treatments in both plantings. The CPH × urea interactions resulted in significant variations in amaranthus height, number of leaves and shoot biomass among the treatments. The growth parameters observed at 0 kg CPH × 60 kg N ha-1 urea were significantly higher than other treatments but not different from CPH at 60 kg N ha-1 × 60 kg N ha-1 urea and CPH at 30 kg N ha-1 × 30 kg N ha-1 urea applications in both plantings. Consequently, CPH powder at 30 kg N ha-1 with urea at 30 kg N ha-1 was considered appropriate for sustainable amaranthus production.